Emotion regulation – natural reward strategy linkage and its impact on sales performance: the mediating impact of salesmanship skills. Issue 3 (3rd April 2018) - Singh, Ramendra; Singh, Rakesh Kumar; Banerji, Diptiman
Abstract : Purpose: In the context of an emerging market, this paper empirically investigates the direct as well as the indirect impact of natural reward strategies (NRS) on the sales performance of B2B sales force. It also investigates the mediating impact of salesmanship skills on the NRS–sales performance linkage. Design/methodology/approach: Structural equation modeling (using AMOS 18 software) is used to analyze the data collected, using a survey questionnaire from a sample of 317 B2B salespersons of a single media firm in India. Findings: Results indicate that NRS are influenced primarily by a salesperson's emotion regulation abilities, while salesmanship skills partially mediate in the NRS–performance relationship. Research limitations/implications: The study results are based on convenience sampling, which may limit the theoretical generalization of the results across all emerging markets. Originality/value: It is one of the earliest studies in the B2B sales literature that integrates multiple theoretical perspectives from job-demands-resources theory, self-regulation theory, motivation and skills theory and social cognitive theory. These theories have been synthesized; then they have been used to develop and test the impact of emotional regulation on NRS components of self-leadership among salespersons, and its subsequent direct impact on sales performance, as well as mediating impact via salesmanship skills.